(untitled) (Bangladesh Journal of Medical Science, 2024)
Tuberculosis is an infectious disease that involves any organ. However, the primary pituitary tuberculosis is an extremely rare disease. Intracranial tuberculomas account for 0.15-5% of intracranial space-occupying lesions, of which, pituitary as the primary site is unusual, and easily misdiagnosed as pituitary adenoma. In this setting, the late diagnosis can result in permanent endocrine dysfunction. We report the case of a 28-year-old woman who presented to the endocrinology department with complaints of progressively increasing headache for 1 month and double vision. On the clinical examination, the patient was conscious and oriented. The routine hematological and biochemical workup showed an increased erythrocyte sedimentation rate (ESR) and increased prolactin levels. MRI scan of Brain reveals Pituitary macroadenoma with impingement upon the optic chaisma, no other significant abnormality is detected in the brain. No other radiological and/or clinical clue that could elicit the suspicion of pulmonary or extrapulmonary lesions of tuberculosis was found. The Endoscopic Transnasal Transphenoidal Surgery was done. The histopathological examination of multiple irregular tissue from excised tumor was Granulomatous inflammation and the final diagnosis of pituitary tuberculoma was made. We report this rare case of pituitary lesion that may be included in the differential diagnosis of sellar lesions to avoid unnecessary surgical interventions, especially in regions where the disease is endemic. Bangladesh Journal of Medical Science Vol. 23 No. 03 July’24 Page : 864-868